Shadowgrams of a dense micro-capillary plasma obtained with a table-top soft X-ray laser - Moreno, C. H., author; Marconi, Mario Carlos, author; Shlyaptsev, Vyacheslav N., author; Rocca, Jorge J., author; IEEE, publisher (Colorado State University. Libraries, 1999)
A sequence of high resolution shadowgrams that map the evolution of the plasma of a 380 μm diameter microcapillary discharge was obtained using a very compact 46.9 nm laser. These images are the first plasma diagnostics data obtained using a table-top soft X-ray laser.
Keywords: capillary discharges; shadowgraphy; soft x-ray diagnostics; soft x-ray lasers